2021
DOI: 10.1371/journal.pmed.1003813
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of 2-dose heterologous Ad26.ZEBOV, MVA-BN-Filo Ebola vaccination in healthy and HIV-infected adults: A randomised, placebo-controlled Phase II clinical trial in Africa

Abstract: Background We investigated safety, tolerability, and immunogenicity of the heterologous 2-dose Ebola vaccination regimen in healthy and HIV-infected adults with different intervals between Ebola vaccinations. Methods and findings In this randomised, observer-blind, placebo-controlled Phase II trial, 668 healthy 18- to 70-year-olds and 142 HIV-infected 18- to 50-year-olds were enrolled from 1 site in Kenya and 2 sites each in Burkina Faso, Cote d’Ivoire, and Uganda. Participants received intramuscular Ad26.ZE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 18 publications
5
69
0
Order By: Relevance
“…Robust EBOV GP-specific binding and neutralising antibody levels were observed in these younger age groups, consistent with those reported in adults [ 11 16 ], with higher responses observed with a longer time interval between the 2 doses (56 versus 28 days). Although not statistically significant, greater responses in the younger age cohort were also detected, in line with our previous observations in an Ad26.ZEBOV, MVA-BN-Filo study in Sierra Leone [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Robust EBOV GP-specific binding and neutralising antibody levels were observed in these younger age groups, consistent with those reported in adults [ 11 16 ], with higher responses observed with a longer time interval between the 2 doses (56 versus 28 days). Although not statistically significant, greater responses in the younger age cohort were also detected, in line with our previous observations in an Ad26.ZEBOV, MVA-BN-Filo study in Sierra Leone [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…We have previously reported that in adults, the heterologous 2-dose Ad26.ZEBOV, MVA-BN-Filo vaccine regimen against EVD is safe, well tolerated, and immunogenic in several Phase I and II trials [ 11 16 ]. The present report confirms those observations in 12- to 17-year-old and 4- to 11-year-old participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations